2020
DOI: 10.1111/jth.14820
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia

Abstract: A recently published article by Dr. Tang and colleagues on "Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia" highlighted that disseminated intravascular coagulation is common severe respiratory failure patients with Novel Coronavirus (Covid-19). 1 Covid-19 infection leading to pneumonia and severe acute respiratory distress syndrome (ARDS) was first reported in Wuhan, Hubei Province, China, and has subsequently spread to almost all other countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
180
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 6 publications
(2 reference statements)
16
180
0
12
Order By: Relevance
“…The monitoring of anticoagulant treatment should be achieved through anti-Xa measurement, owing to changes of standard hemostasis parameters in this particular pathology. Although Tang et al [3] suggested that anticoagulant therapy mainly with LMWH appears to be associated with better prognosis in severe COVID-19 patients meeting SIC criteria or with markedly elevated D-dimer, higher anticoagulation targets than usual should probably be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The monitoring of anticoagulant treatment should be achieved through anti-Xa measurement, owing to changes of standard hemostasis parameters in this particular pathology. Although Tang et al [3] suggested that anticoagulant therapy mainly with LMWH appears to be associated with better prognosis in severe COVID-19 patients meeting SIC criteria or with markedly elevated D-dimer, higher anticoagulation targets than usual should probably be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, prothrombin time, aPTT and antithrombin remained within normal ranges in 120 (80%), 108 (72%), and 100 patients (66.7%), respectively, which explains the normal JAAM-DIC (< 4 points) in 144 patients (96%) and normal ISTH (< 5 points) scores in all patients. Median scores were 0 [0; 1] and 2 [2,3] points for JAAM-DIC and ISTH scores, respectively. Only 6 patients (2.7%) had a positive JAAM-DIC score, and none had a positive ISTH score.…”
Section: Coagulation Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the rst case with SARS-CoV-2 was published in December 2019, the laboratory-con rmed cases are continuously escalating day to day and spread like wild re to more than 200 countries and territories [5,6]. COVID-19 cases are frequently associated with respiratory and multiorgan dysfunction that result in deaths [7][8][9][10]. Accordingly, the use of antiviral drugs in patients with this disease have triggered questions and whether currently antiviral drugs could be effectively cured this disease prompts a critical consideration.…”
Section: Introductionmentioning
confidence: 99%